IMPLEMENTASI GAYA KEPEMIMPINAN TRANSFORMASIONAL KEPALA TAMAN KANAK-KANAK ALFASIHI - Suhartini; Gusnawati; Rosmini; Damayanti; Andi Hartati; Syamsiar; Besse Herlina (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This paper discusses the implementation of transformational leadership by the Principal of Alfasihi Kindergarten (TK Alfasihi). Transformational leadership is considered crucial in creating an innovative and adaptive educational environment, particularly at the early childhood education level. This research employs a qualitative approach with a case study method to analyze how the Principal of TK Alfasihi applies the four dimensions of transformational leadership: idealized influence, inspirational motivation, intellectual stimulation, and individualized consideration. Data were collected through observations, interviews with the principal and teachers, and document analysis. The results show that the Principal of TK Alfasihi has successfully implemented a transformational leadership style, which has had a positive impact on teacher performance, student learning motivation, and the overall organizational culture of the school. The implications of these findings provide insights into the importance of transformational leadership in enhancing the quality of early childhood education.